METHOD FOR ASSESSING THE READINESS OF HIGH-TECH PRODUCTS FOR INDUSTRIAL PRODUCTION - A. M. Batkovskiy; A. V. Leonov; A. Yu. Pronin (Статистика и экономика, 2018)
Purpose of the study. High-tech products are complex products created on the basis of the application of unique production processes, or products that realize their consumer functions using the latest physical and technical effects. The aim of the study is to develop a new method for assessing the readiness of high-tech products for production. The creation of high-tech products is a very complex and expensive process, which involves the formation of a scientific and technical reserve with the wide use of scientific achievements. For example, the process of creating a scientific and technical reserve in the interests of conducting research and development work includes the stages of the formation of scientific, scientific & technological and industrial-technological reserves. Therefore, the assessment of the readiness of high-tech products for industrial production has specific features.Materials and methods. In the conditions of insufficient funding to create a scientific and technical base and the fundamental impossibility of carrying out fundamental scientific research on a "wide spectrum," the current task is to form such a rational research composition that would allow the creation of high-tech products with high quality and a high degree of the readiness for industrial production. At present, the methodological tools for assessing the readiness of high-tech products for industrial production is at the first stage of development, although the relevance of such estimates arises in the process of justifying almost any experimental design work. This ensures an improvement in the quality of the products created. Improving the quality of high-tech products is a multifaceted problem. The main quality components are the technical level in the product documentation, the degree of implementation of this level in the manufacturing process of the product. The research is based on the theory of economic science. A method is proposed for assessing the readiness of high-tech products for industrial production, including all its stages: from the formation of the conceptual technological scheme of the product to the calculation of the level of production and technological readiness. An important feature of the developed method is the use of a mathematical apparatus, including the classical method of expert evaluations, taking into account the author's version of its modification in relation to the problem under consideration.Results. The developed method is based on the presentation of a promising product of high-tech products in the form of a set of functional and technological blocks that include a variety of different technologies and the use of expert assessments to assess the level of readiness of production technologies and the technological readiness of the product for industrial production. The proposed method has scientific novelty, which determines the representation of a promising product of high-tech products in the form of a set of functional and technological blocks, each of which includes a number of different technologies (both existing and new) that allow for their joint use (operation) required characteristics of high-tech products.The conclusion. Practical use of the developed method of evaluation seems to be the most effective in the framework of modern concepts of managing high-tech enterprises. The offered method can be used at preparation of industrial-technological reserve for perspective products of high-tech production. The efficiency of the developed method for assessing the readiness of high-tech products for industrial production is demonstrated on a numerical illustration and tested in the process of managing the production of this product.